ALGHAZALI DAN KESUKSESANNYA DALAM MENYEBARKAN TEOLOGI SUNNI ASY’ARI - Alma'arif alma'arif (UIN Raden Mas Said Surakarta, 2019)
This article aims to describe and analyze the success of Alghazali in spreading Sunni Asy’ari theology. Based on library studies, with Jurgen Habermas's communicative action theory approach, the results of the study show that Alghazali's success in spreading Sunni Asy'ari theology, both during the Abbasids and afterward, is different from the approach taken by his predecessor theologians. If earlier theologians had prioritized the dominated and indoctrinated model of power relations in spreading theology, Alghazali had a different way. Communicative patterns of action that promote skepticism or always provide space for each individual to test the validity of an accepted truth; take action and control over the situation with intuitive knowledge; and utilizing public spaces with various forms of language expression, especially through various works, so that the listener/reader can communicate actively, finally succeeded in bringing Sunni Asy'ari theology to be more known and accepted by the wider community, and made Alghazali as one of the famous figures of it.